Upaya Pemerintah Provinsi Bali Mengatasi Isu Health Security Pandemi Covid-19 di Pelabuhan Gilimanuk, Negara, Bali dan di Pelabuhan Benoa, Badung, Bali - Parameswari, Anak Agung Ayu Intan (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 2 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONALDO - 10.24843/JIWSP.2023.v05.i02.p06, 2023)
The COVID-19 pandemic saw disruptions to health security in global scale. Moreover, the COVID-19 is the consequence of a borderless world which can deliver treacherous diseases that attack humans life. At the same time, the Government of Bali is intensively improving policies in the tourism sector to convey good outcomes for the country's economy, primarily for boost the number of tourist. This expectancy must be put aside considering that multiple countries have closed the entry and exit routes of tourists to their countries to prevent the spread of the Coronavirus. This study aims to explain how the Bali Government's endeavors to implement policies for accomplish health security through Bali's entrances which focus on the Gilimanuk Port and Benoa Harbor by reducing the number of foreign and domestic tourists visiting Bali. This study uses a qualitative descriptive method with a health security framework. This study obtained an answer that the government's endeavors through internal and external policies, it's caused the number of crossing passengers from 2020-2021 decreased, which strongly demonstrates the significance of the policies formed by the Bali Provincial Government to the Districts on the border areas with the strict supervision, especially on Benoa Port and Ketapang-Gilimanuk Port to avoid the wider impact on state security